The suffering servant of the Lord: a prophecy of Jesus Christ : an exposition of Isaiah 52:13-53:12 - MacLeod, David J. (Wipf & Stock, 2019)
From Golgotha to God's right hand: Isaiah 52:13-15 -- Israel's rejection of the Servant of the Lord: Isaiah 53:1-3 -- The vicarious sufferings of the Servant of the Lord: Isaiah 53:4-6 -- The ignominious yet voluntary death of the Servant of the Lord: Isaiah 53:7-9 -- The resurrection and reward of the Servant of the Lord: Isaiah 53:10-12 -- Appendices -- The Suffering Servant of Isaiah 53 in the Jewish interpreters -- Healing and the atonement in Isaiah 53 -- Popular objections to the doctrine of substitution -- Christian hymnody and the doctrine of substitution -- A composer, a disgraced actress, a debtor's prison, and Isaiah 53.